The Impact of Mobile Health Applications on the Nutritional Status of Breast Cancer Patients: A Literature Review - Beni Sepila; Widia Lestari; Juniar Ernawati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Breast cancer is the leading cause of cancer-related deaths in women worldwide. Patients undergoing chemotherapy frequently experience nutritional deterioration, which negatively impacts treatment outcomes and quality of life. Mobile health (mHealth) applications offer an innovative approach to supporting nutritional management in this population. To synthesize scientific evidence on the effect of mHealth applications on the nutritional status of breast cancer patients and survivors. A literature review was conducted following the PRISMA 2020 guidelines. Searches were performed in PubMed, ScienceDirect, and Google Scholar for articles published between 2020 and 2026. Inclusion criteria included RCTs, quasi-experimental, or experimental studies examining mHealth interventions on the nutritional status of breast cancer patients. From 270 articles identified, 6 met the inclusion criteria after systematic screening. All six studies demonstrated that mHealth interventions showed promising positive effects on nutritional outcomes. Key findings included weight reduction, improved BMI, enhanced diet quality, increased consumption of fruits, vegetables, and protein, and improved self-efficacy in dietary management. mHealth applications demonstrated high feasibility and acceptability among participants. These findings should be interpreted cautiously, as most studies were pilot or feasibility studies with small sample sizes. mHealth applications show promising potential in improving nutritional status and eating behaviors in breast cancer patients and survivors. Further large-scale RCTs with standardized nutritional outcome measures and longer follow-up periods are warranted to establish robust evidence.